Fate of the inhaled smoke particles from fire scenes in the nasal airway of a realistic firefighter: A simulation study. Issue 4 (3rd April 2019) - Xu, Xiaoyu; Shang, Yidan; Tian, Lin; Weng, Wenguo; Tu, Jiyuan
Abstract: Understanding the inhalation, transport and deposition of smoke particles during fire missions are important to evaluating the health risks for firefighters. In this study, measurements from Underwriters Laboratories' large-scale fire experiments on smoke particle size distribution and concentration in three residential fire scenes were incorporated into models to investigate the fate of inhaled toxic ultrafine particulates in a realistic firefighter nasal cavity model. Deposition equations were developed, and the actual particle dosimetry (in mass, number and surface area) was evaluated. A strong monotonic growth of nasal airway dosages of simulated smoke particles was identified for airflow rates and fire duration across all simulated residential fire scene conditions. Even though the "number" dosage of arsenic in the limited ventilation living room fire was similar to the "number" dosage of chromium in the living room, particle mass and surface area dosages simulated in the limited living room were 90–200 fold higher than that in the ventilated living room. These were also confirmed when comparing the dosimetry in the living room and the kitchen. This phenomenon implied that particles with larger size were the dominant factors in mass and surface area dosages. Firefighters should not remove the self-contained breathing apparatus (SCBA) during fire suppression and overhaul operations, especially in smoldering fires with limited ventilation.